Prevalence and determinants of dyslipidemia among adults in the community: A cross-sectional study in a selected province, Sri Lanka - Hapugahapitiye Mohottalalage Renu Kalhari Geethani Nandasena; Tennakoon Mudiyanselage Sampath Udaya Bandara Tennakoon; Dissanayake Mudiyanselage Priyantha Udaya Kumara Ralapanawa (Elsevier, 2023)
Background: Dyslipidemia is an important modifiable risk factor for cardiovascular diseases (CVDs). The aim of the present study was to assess the prevalence and determinants of dyslipidemia among adults in a rural community in Sabaragamuwa province of Sri Lanka. Methods: A descriptive cross-sectional study was conducted among adults aged between 30 and 60 years. Participants were selected using a three staged random sampling method. The WHO STEPS wise approach was used to collect data. Chi-square tests, independent sample t-test and binary logistic regression were used to obtain prevalence and determinants for dyslipidemia. Results: There were 366 participants with a male to female ratio of 1:2.1. Mean age was 45.2 years (SD = 8.8). The prevalence of dyslipidemia was 64.2 % overall, with 39.9 %,29 %,37.7 %, and 21.3 % for high total cholesterol (TC), low high density lipoprotein cholesterol (HDL-C), high low density lipoprotein cholesterol (LDL-C), and high triglycerides respectively. Increasing age, physical inactivity, low fruit and/or vegetable consumption and higher BMI were significantly associated with dyslipidemia. Conclusion: Two in every three adults in the community have dyslipidemia. High LDL-C was the most prevalent component of dyslipidemia followed by low HDL-C. Multisectoral intervention strategies are needed considering the predictors identified to combat with high prevalence of dyslipidemia in this population.